2004
DOI: 10.1557/proc-845-aa5.31
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Sintering and Microstructural Characterization of Nanocrystalline Hydroxyapatite Composites

Abstract: Nanocrystalline hydroxyapatite (HAp) exhibits better bioactivity and biocompatibility with enhanced mechanical properties compared to the microcrystalline counterpart. In the present work, nanocrystalline hydroxyapatite was synthesized by wet chemical method. Sintering was carried out with nanocrystalline alumina as additive, the content of alumina being varied from 10 to 30 wt% in the composite. For 20 and 30 wt % A1 2 0 3 , hydroxyapatite decomposed into tricalcium phosphate (TCP) above the sintering tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The ceramic materials were investigated with TEM (JEM 2100, JEOL, Japan). For this purpose, the ceramic samples were grounded in an agate mortar, the particles were sieved through nylon sieve with 30 µm mesh and investigated as powders with preparing of the suspensions in isopropyl alcohol, which were applied on the copper mesh coated with a carbon film according to the scheme described in [31]. The phase composition was confirmed by the electron diffraction (ED) data obtained by TEM.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…The ceramic materials were investigated with TEM (JEM 2100, JEOL, Japan). For this purpose, the ceramic samples were grounded in an agate mortar, the particles were sieved through nylon sieve with 30 µm mesh and investigated as powders with preparing of the suspensions in isopropyl alcohol, which were applied on the copper mesh coated with a carbon film according to the scheme described in [31]. The phase composition was confirmed by the electron diffraction (ED) data obtained by TEM.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…In all the composite samples, MFA decomposed into β-tricalcium phosphate (β-TCP) during TSS. It has been shown that this decomposition and the consequent biphasic ceramic formation are favorable to bone regeneration and repair (Viswanath et al, 2005). The XRD patterns for the sintered MFA/alumina composites via TSS are shown in Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 99%